Application of technology for 3D printing in education - Asenova, Asya; Afzaly, July (Yearbook Telecommunications, 2018)
Although 3D printing was created more than thirty years ago, there are nowadays more and more applications of this type of real-world printing. One of the main areas of increasing interest in 3D printing is in the field of education and its application in various subjects and with different age groups. The implementation of technology in training provides a constructivist approach, i.e. a person actively builds what they know and does not receive knowledge passively.